Social Closure: Unpicking and Rethreading a Sense of Fragility - Woods, Betty (Elizabeth) (Auckland University of Technology, 2011)
The primary aim of this politically informed visual arts project 'Social Closure' is to investigate poignant metaphors to highlight visually the phenomenon ‘small town industrial decline’. In this practice-led research my investigation is underpinned by personal anecdotes together with current social science research carried out in my home town of Kumara, on the West Coast of the South Island where I lived from 1983 until 2006. Cust (2008) states that “[c]urrently much of the township’s infrastructure and essential services have closed or become derelict after the industries it was built around became no longer operational” (p. 4). To unpick and rethread a sense of the fragility that commonly occurs in these circumstances I have explored the use of textiles and clothing that reference the situations that I witnessed in domestic, industrial and leisure activities in Kumara during the 1980s. I used this method to investigate ways of representing the consequences of social closure on the people in the community. Using situation-based artwork as a communicative language, I have sought to create an additional space to social science research to provide a deeper understanding of the issues faced by inhabitants of small industry dependant communities experiencing decline.
Keywords: Textile art; Installation art; Small town industrial decline; Kumara